I-V Characterization and Electrical Performance Analysis of Undoped, N-Type, and P-Type Silicon for Semiconductor Applications - Anyaora , Sunday Chimezie; Nwokeocha, Tochukwu Obialor; Nwaokafor, Innocent Chisom Chukwuma-; Takim , Stephen A. (Journal of Computer Science and Research (JoCoSiR), 2024)
Silicon remains the backbone of modern semiconductor technology; however, its intrinsic electrical limitations, such as low conductivity and restricted charge carrier concentration, constrain device performance. To enhance its functionality in electronic and photovoltaic applications, doping with suitable impurities is essential. This study focused on the I–V characterization and electrical performance analysis of undoped, N-type, and P-type silicon to assess the effect of doping on charge transport behavior. The experiment involved I–V characterization of intrinsic, N-type, and P-type silicon samples using precise materials, contact metals, and cleaning agents to ensure accuracy. A DC power supply, Source Measure Unit (Keithley 2400), and four-point probe station were employed for voltage application and current measurement. Samples were cleaned, coated with silver or aluminum contacts, annealed, and stored under nitrogen to prevent oxidation. I–V measurements were conducted under controlled environmental conditions, using calibrated equipment and multiple readings for accuracy. Data analysis in MATLAB included filtering, curve fitting, and extraction of key parameters like resistance and ideality factor to compare doped and undoped samples. The I–V characterization revealed clear differences between undoped and doped silicon samples. The undoped silicon exhibited Ohmic behavior with low conductivity ((5.3±0.2)×10⁻⁵ Ω⁻¹), while the N-doped ((1.4±0.1)×10⁻³ Ω⁻¹) and P-doped ((9.7±0.8)×10⁻⁴ Ω⁻¹) samples showed rectifying characteristics. N-type silicon displayed a lower turn-on voltage (0.65±0.02 V) than P-type (0.72±0.03 V), reflecting higher electron mobility. Ideality factors near unity (1.12 and 1.18) indicated diffusion-controlled transport. Conductivity improved 26-fold for N-type and 18-fold for P-type compared to intrinsic silicon, confirming doping’s strong influence on charge carrier concentration and validating measurement accuracy (standard deviation <3%). The study concludes that controlled doping significantly improves silicon’s electrical properties, making it more suitable for high-efficiency semiconductor and photovoltaic device applications.